Standardization of surface sterilization protocol of field grown stevia rebaudiana prior to in vitro clonal propagation - Urbi, Zannat; Zainuddin, Zarina (Universiti Teknologi Malaysia, 2015)
The high demand of Stevia rebaudiana, commonly known as Stevia encourages people for commercial-scale cultivation. In vitro clonal propagation is a potential alternative for conventional propagation due to its advantages. However, microbial contamination is a constant problem for in vitro clonal propagation of field grown plant. Therefore, the aim of this study was to establish an effective surface sterilization protocol for Stevia prior to in vitro propagation. Two disinfecting agents, NaOCl and HgCl2 with different concentrations and various exposure times were tested for surface sterilization of shoot tips and nodal explants. Results show that treatment of explants with NaOCl was more effective compared to HgCl2 and 5% NaOCl for 10 minutes with 0.2% carbendazim (fungicide) pre-treatment showed least contamination and highest survival rate. Fungal contamination was observed to be a main problem in this study and it occurred within 2-3 days of inoculation, leading to the death of the explants.